Half-Earth or Whole Earth? Radical ideas for conservation, and their implications. Issue 3 (5th December 2016) - Büscher, Bram; Fletcher, Robert; Brockington, Dan; Sandbrook, Chris; Adams, William M.; Campbell, Lisa; Corson, Catherine; Dressler, Wolfram; Duffy, Rosaleen; Gray, Noella; Holmes, George; Kelly, Alice; et al.
Abstract: We question whether the increasingly popular, radical idea of turning half the Earth into a network of protected areas is either feasible or just. We argue that this Half-Earth plan would have widespread negative consequences for human populations and would not meet its conservation objectives. It offers no agenda for managing biodiversity within a human half of Earth. We call instead for alternative radical action that is both more effective and more equitable, focused directly on the main drivers of biodiversity loss by shifting the global economy from its current foundation in growth while simultaneously redressing inequality.